Electrochemical probe for total determination and speciation of selenium (IV& VI) species in water, drug formulations and foodstuffs using Thoron–I as selective chelating agent - H. Alwael (Results in Chemistry)
The present study reports a highly sensitive, selective and cost effectiveness-sensing probe for total determination and speciation of selenium (IV & VI) species in complex matrices. The established probe was based upon controlled electrolysis of Se4+-Thoron–I chelate at hanging mercury-dropping electrode (HMDE) combining adsorptive differential pulse-adsorptive cathodic stripping voltammetry (Ads DP-CSV) and measuring the consequent cathodic peak currents (Ip,c) at −0.5 and − 1.1 V vs. Ag/AgCl electrode in aqueous solution of pH 2. At the optimal conditions of peak potentials at −0.5 and − 1.1 V, the plots of Ip,c versus Se4+ concentration were linear over the concentrations range 6.3 × 10−9–8.2 × 10−8 and 5.0 × 10−12 - 1.45 × 10−10 M with limits of detection (LOD) and quantification (LOQ) of 1.6 × 10−12 M and 5 × 10−12 M of Se4+, respectively. The sensing probe was favorably used for detection of trace levels of Se6+ after reduction to Se4+. The probe also displayed excellent sensitivity and selectivity towards detection of selenium species in water, foodstuffs and drug formulations. The probe was validated by analysis of selenium in certified reference material (CRM, IAEA- Soil-7) and in drug formulations. The average recoveries for the spiked water samples were ranged from 99.4 ± 0.60 to 110.0 ± 6.3. The probe was also validated by comparing the results with the inductively coupled plasma–optical emission spectrometry (ICP-OES) data using Student t and F tests at 95 % probability. Sequential and total determination of trace levels of inorganic Se4+and/or Se6+ was also achieved by the proposed probe.